Treatment of extreme overhydration in an adolescent boy with idiopathic nephrotic syndrome - Szydłowski, Andrzej; Szydłowska, Anna; Masłocha, Agata; Morawiec-Knysak, Aurelia; Broll-Waśka, Katarzyna; Jędzura, Agnieszka; Szczepańska, Maria (Pediatria Polska - Polish Journal of Paediatrics, 2022)
The key factors in the diagnosis of nephrotic syndrome (NS) in children are as follows: proteinuria > 50 mg/kg/day and serum albumin level ≤ 30 g/l (prevalence: 16/100,000; incidence: 2–7/100,000 cases per year). Glucocorticoids are preferred to obtain remission. Diuretics and albumin infusions are used in oedema reduction. In cases of extreme overhydration, renal replacement therapy (RRT) is advised. A 16-year-old boy with no past medical history was admitted in critical condition due to massive oedema and anuria. Standard NS treatment was introduced on admission. The patient underwent continuous RRT combined with loop diuretics and albumin administration. Thirty-six litres of ultrafiltrate was achieved. No relapse was observed within 6 months of discharge. The presented case is unusual due to the enormous oedema, reaching approximately 30% of the initial body weight, which led to a vital clinical problem. The use of continuous RRT combined with steroid therapy allowed for a safe evacuation of the oedema and remission.